The ultrasound perspective of the diagnosis of deep endometriosis - Freitas, Kelvin Augusto Leite; Rezende, Izabela Silva; Freitas, Cássia Lorena de Oliveira Leite e; Barros , Cynthia Roberta Torres de; Guimarães, Raquel Meirelles Gaspar Coelho (Seven Editora, 2024)
Endometriosis is one of the main conditions causing chronic pelvic pain and infertility in the female population worldwide¹, affecting and negatively impacting quality of life in several age groups. The process of diagnostic investigation of endometriosis is challenging, especially in the public health network since it is extremely costly¹¹. Among the available methods, vaginal ultrasound with bowel preparation (USGTVPI) has statistically similar detection of deep endometriosis. Data were collected from 14 (fourteen) patients treated at the Gynecological Surgery outpatient clinic of the Regional Hospital of Taguatinga (HRT) in 2022 and 2023.When analyzing the results of the questionnaire, it is noted that deep endometriosis was diagnosed via USGTVPI in many patients with menstruation disorders and pain complaints. In this context, the USGTVPI emerges as a great possibility in the technological arsenal to aid in the perception of pelvic lesions, considering that it is an easily accessible and less expensive method than other available methods, such as laparoscopic laparotomy and contrast-enhanced pelvic MRI. At this juncture, there is a need to discuss the insertion of the method as an alternative diagnosis of the pathology, especially in the Unified Health System (SUS). DOI:https://doi.org/10.56238/sevened2024.007-011